A placental dilemma: exaggerated placental site tumour - Jayakrishnan, Niranjana; Jayakrishnan, Krishnapillai (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Exaggerated placental site is defined as a non-neoplastic lesion characterized with infiltration of extravilleous intermediate trophoblasts into the myometrium and the walls of blood vessels of the normal placental implantation area. They are commonly seen following spontaneous or elective abortions and present rarely as a cause of third stage bleeding or post-partum hemorrhage. A case of an exaggerated placental site is presented in this article. It is aimed to review the current information about this rare condition. We encountered a case of exaggerated placental site (EPS) reaction following evacuation of a missed abortion in a 34 year old lady. She presented to us, with bleeding per vaginum, not responding to medical management. Hysteroscopy was done and a fleshy mass noted in the posterior wall was resected and sent for examination. Histopathological report was an exaggerated placental site. EPS is a type of trophoblastic lesion and can cause worry to the surgeon at a first glance. Its clinical course has been reported by few. Its diagnosis is mainly by ultrasound and histopathology.